A Novel Bioscaffold Material-based Transplantable Liver Reconstruction - Hu, Deyu; Wu , Zhenyu; Lai, Jiejuan; Yan, Min; Chen, Quanyu; Zhang, Leida; Zhang, Hongyu; Bai, Lianhua (New Horizons in Medicine and Medical Research Vol. 12, 2022)
End-stage liver disease (ESLD) is an important cause of death worldwide and the interest in tissue engineering with decellularization/recellularization approach is currently promising one for liver regeneration. The decellularized scaffold generated from normal whole liver (nDLS) preserves the original orchestral structure and bioactive chemicals of the liver, and has the potential to create a de novo liver that is fit for transplantation after recellularization. As the lack of active ECM of the nDLS impacting seed cell survival and hemocompatibility are key hurdles for functional liver reconstruction, a novel approach needs to be formulated. This chapter provides a comprehensive outlook on how these drawbacks can be turned into the current challenges in the field, and put forward a few potentially viable options to address these challenges, mainly focusing on a novel decellularized liver scaffold (rDLS)-based liver engineering strategy. We speculate that the primary concepts necessary for advantages of the rDLS in liver reconstructing processes as compared to the nDLS. Additionally, the criteria for major obstacles in using rDLS are covered in detail.